The Role of Multimedia in Developing Ecotourism Branding of Yogyakarta Special Region (DIY) - Damiasih, Damiasih; Isdarmanto, Isdarmanto (Jurnal Penelitian Pariwisata, 2019)
In the current millennium and globalization era, the multimedia aspect has a very important role in the dissemination of all information and news through faster and more effective information technology. This is very important to learn, because every professional individual must be able to access all kinds of diverse programs in multimedia applications. This study uses qualitative research to understand the problems deeper. The purpose of this research is to find out the positive implications of multimedia in developing regional ecotourism, and to anticipate the negative implications of the multimedia in spreading false news. Spreading public lies can create serious problems for the community. This results in the emergence of contradictions, hostilities and legal problems that ads to crime. The role of multimedia is expected to be able to provide many benefits in the exchange of information, technology in aspects of life, culture, politics and social economy, especially for the development of ecotourism branding in the Special Region of Yogyakarta.